Analysis of Student Difficulties in Learning Mathematics in Elementary School Lower Grades - Saputri, Sela; Ruqoyyah, Siti; Rohaeti, Euis Eti (Kopertis Region IV Jabar and Banten, 2024)
One of the subjects that students must master is mathematics. This study aims to determine the difficulties experienced by students, especially in low grades, during the teaching and learning process of mathematics subjects. The method used in this research is the descriptive-qualitative method. Based on interviews that have been conducted, information has been obtained that some students tend to have some difficulties with basic skills such as subtraction, multiplication, and fractions. The causes of the obstacles experienced by students are that math subjects are considered scary lessons, there is a lack of use of learning media, and students are used to routine problems. Efforts made by teachers to overcome the obstacles that occur include using various learning media, peer tutors, additional support for students who need it, selecting strategies, approaches, methods and techniques to support learning to be more effective